Improving the Environmental Sustainability of Polyketides Colorants Production by Talaromyces Strain through Better Hydrodynamic Design in Bioreactors - De Oliveira, Fernanda [UNESP]; Zapata-Boada, Santiago; Da Silva, S. S.; Cuéllar-Franca, Rosa M.; Santos-Ebinuma, Valéria C. [UNESP] (American Chemical Society (ACS), 2022)
One important step toward the commercialization of microbial-derived colorants is the reproducibility of the cultivation stage in bench-scale bioreactors as well as improving the hydrodynamic design in bioreactors. Aiming to address these technical barriers, Talaromyces amestolkiae was cultivated in a 4 L stirred-tank bioreactor using two types of impellers (Rushton turbine (RT) and Elephant ear (EE) impellers) and aeration modes (cascading and constant airflow) to assess their effects on red colorant production. The results showed that EE under constant airflow (4.0 L min-1) promoted the maximum red colorant formation (28.7 UA500nm), thus improving the reproducibility of the process. The volumetric oxygen transfer coefficient of culture broth was correlated to cell morphology, which was a result of the impeller geometry of EE through the shear conditions impacting the fungi cells. The hairy pellet morphology favored nutrient and oxygen uptake and allowed an improvement in the colorant's synthesis. Life cycle assessment was also carried out to identify opportunities for improving the best process design from an environmental sustainability perspective. For example, the total climate change and primary energy demand were estimated at 31.11 kg CO2eq./g red colorant and 830.7 MJ/g red colorant, respectively, with the cultivation stage contributing with 65 and 63% of these impacts. The electricity consumption was identified as the main hotspot in this stage, a trend that was observed across all other impact categories. This can be improved by optimizing cultivation lengths combined with the use of low carbon electricity sources. These findings ensure a step forward toward the scaling-up at the industrial scale of the T. amestolkiae cultivation for the production of bio-based colorants in an environmentally sustainable way.
Keywords: cell morphology; colorant; life cycle assessment; stirred tank bioreactor; Talaromyces amestolkiae